ANALYSIS OF SCIENCE PROCESS SKILLS OF HIGH SCHOOL STUDENTS IN MEDAN CITY - Mukra, Rizal; Nuzalifa, Yosie Ulfa; Septiani, Findi; Rahmawati, Suci (Universitas Negeri Medan, 2024)
This research aims to determine the results of science process skills in four state schools in Medan City. This type of research is descriptive with a quantitative approach. Samples were obtained from 4 schools using Cluster Sampling based on the criteria for State High Schools in Medan City, namely MAN 1, MAN 2, State High School No. 3, and State High School No. 4 Medan. Using science process skills test question for class XI student on Biology subject. Using descriptive analysis technique by calculating average data values. The result of this research is that students' science process skills at four state schools in Medan City average 74.74. The highest value is in the communication aspect and the lowest is in planning the experiment.